Minimal reference: The use of pronouns in Finnish and Estonian discourse - Laury, Ritva (Studia Fennica Linguistica, 2005)
"This book presents some of the most recent research on Finnish and Estonian pronouns and other minimal forms of reference. The articles deal with features particular to the pronoun systems of Finnic languages, such as logophoricity and the use of demonstratives for human referents, as well as other topics of current interest in research into the nature of pronominal reference, in particular the contextual, interactive and grammatical factors which influence the use and interpretation of pronouns. An international group of authors approach these questions from several theoretical frameworks including psycholinguistics, syntax, conversation analysis and discourse analysis. The volume is the first collection of articles on this topic published in English. Authors include Outi Duvallon, Marja Etelämäki, Päivi Juvonen, Elsi Kaiser, Lea Laitinen, Renate Pajusalu, Eeva-Leena Seppänen, and the editor, Ritva Laury. "